DAMPAK PERKEMBANGAN PEMBANGUNAN SARANA AKOMODASI WISATA TERHADAP PARIWISATA BERKELANJUTAN DI BALI - Evita, Rossi; Sirtha, I Nyoman; Sunarta, I Nyoman (Jurnal Ilmiah Pariwisata; Volume 2 No.1 Hal 109-222 September 2012, 2012)
The tourism industry is one of the largest industries in the world. The tourism industry can absorb the labor force in large numbers, to increase income and economy and can provide a large contribution to a country. As one of the world's largest industry, tourism development is expected to boost the economy so as to improve the welfare of the community in which tourism is developed. The development of tourism must be supported by all aspects and tourism support facilities such as: place of accommodation (accommodation facilities: e.g. hotels, villas, etc.), restaurant, travel agent, money changer, transportation, infrastructure and tourism destinations that are offered to tourists. The aim of this research is to determine how the impact of the construction of tourist accommodation facilities, especially construction of villas in Bali towards sustainable tourism and fatherly looking out strategies that must be done to achieve sustainable tourism in Bali in the future. Type of data used was qualitative and quantitative data obtained from literature study, documentation and interviews via email. The analysis uses descriptive qualitative analysis method. The results showed that in terms of economic development of the construction of the villa has a positive impact on increasing revenue. In addition to the positive impact on increasing revenue, negative impact that posed that is productive agricultural land is reduced so that the diminishing agricultural output each year, and pollution to the environment. In realizing sustainable tourism required an appropriate strategy like development of ecotourism and government policies as well as good cooperation between the government and the tourism industry.
Keywords: dampak, perkembangan sarana akomodasi wisata, pariwisata berkelanjutan